Analisis Hasil Ujicoba Bahan Ajar dengan Konten Nilai Kecerdasan Sosial Materi Vektor dan Gerak Lurus untuk Siswa Kelas X SMA - Suci Indah Putri; Zulhendri Kamus; Asrizal Asrizal (Universitas Negeri Padang, 2018)
In 2013 curriculum contains four types of core competencies. The core competencies include spiritual attitudes, social attitudes, knowledge, and skills. Competence of social attitudes is an important aspect which needed to develop in teaching materials of physics. The purpose of this research was to determine the practicality and the effectiveness of physics teaching materials with the content of social intelligence values on teaching matter of vector addition and linear motion. The type of this research was Research and Development (R & D). The development method which used was Sugiyono R & D model. The object of this research was the teaching material with the content of social intelligence values that was tested to grade X students in SMA Adabiah Padang. The instruments which that used in this research were practicality test sheet and effectiveness test sheet. The form of the effectiveness test sheet were test result sheet and attitude assessment sheet. Data analysis techniques which used were descriptive statistics analysis and comparative test of one group of sample. Based on data analysis, there were two results of this research. First, the use of teaching material with the content of social intelligence values was practice according to physics teachers and students were 91.1 and 76.2 respectively. Second, the use of teaching material with the content of social intelligence values was effective in scientific approach to improve knowledge and attitudes competence of students.